Features and Pricing of Weather Index Insurance —based on rice temperature index insurance in Wangqing county - Lu, Jing (Archives of Business Research, 2019)
In recent years, weather risk has become a major risk for agricultural production, especially for China which has six climate zones and has complex terrain. Due to the high risk of adverse selection, high moral hazard, and high underwriting and claim reasons, traditional agricultural insurance has been unable to deal with weather risk. Weather index insurance immediately emerged. In the paper, after studying the features and pricing methods, it selects Wangqing county 1998-2012 fifteen years meteorological data and rice yield data, chooses the temperature as an index, and use the value of the average daily temperature data and production data to determine the premium rates.